The quiet mother - Arnaldur Indriðason, 1961- (Arnaldur Indriðason, 1961- Detective Konrad novel, 2025)
In this Nordic noir novel, retired detective Konrad becomes involved in a murder investigation when a woman is found dead in her Reykjavík apartment. The case is complicated by the victim's past, including a child she gave up decades earlier, and by links to a long-unsolved murder. As Konrad investigates, he uncovers family secrets, personal betrayals, and hidden lives, confronting both the victim's history and his own. The novel combines crime investigation with psychological insight, exploring themes of guilt, loss, and redemption.